A gender history of Hungarian intelligence services during the Cold War. Issue 2 (2nd July 2020) - Pető, Andrea
ABSTRACT: Based on the examination of the positions and activities of women employees from the interwar period until the 1980s in the accessible archival sources of Hungarian intelligence services, this paper claims that since in intelligence women employees have been deployed as "controlling images" of men. It argues that for women, the intelligence service sector is just like any other paid employment: with time, women were gradually integrated in it; and the level of their involvement reflected the level of women's emancipation in the given society. Women working for the intelligence services had to counter workplace discrimination just like any other female employee in more ordinary jobs. However, intelligence work has an additional special feature: sexism and gender-based discrimination are intrinsic parts of it, because the deployment of femininity as "Otherness" is part and parcel of the trade and the result of deliberate methodological decisions.